2011
DOI: 10.1051/0004-6361/201117529
|View full text |Cite
|
Sign up to set email alerts
|

SDSS DR7 superclusters

Abstract: Context. The study of superclusters of galaxies helps us to understand the formation, evolution, and present-day properties of the large-scale structure of the Universe. Aims. We use data about superclusters drawn from the SDSS DR7 to analyse possible selection effects in the supercluster catalogue, to study the physical and morphological properties of superclusters, to find their possible subsets, and to determine scaling relations for our superclusters. Methods. We apply principal component analysis and Spea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
71
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 98 publications
10
71
0
Order By: Relevance
“…Poor spider-type superclusters are similar to our Local supercluster with one rich cluster and filaments of galaxies and poor groups of galaxies around it (Einasto et al 2007b). Einasto et al (2012a) analysed the structure of rich galaxy clusters in superclusters of different morphologies and showed that clusters in superclusters of spider morphology have higher probabilities of having substructure and their main galaxies have higher peculiar velocities than clusters in superclusters of filament morphology.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Poor spider-type superclusters are similar to our Local supercluster with one rich cluster and filaments of galaxies and poor groups of galaxies around it (Einasto et al 2007b). Einasto et al (2012a) analysed the structure of rich galaxy clusters in superclusters of different morphologies and showed that clusters in superclusters of spider morphology have higher probabilities of having substructure and their main galaxies have higher peculiar velocities than clusters in superclusters of filament morphology.…”
Section: Introductionmentioning
confidence: 62%
“…As a result, the maximum sizes in the sky projection and the velocity dispersions of our groups are similar at all distances. Our initial sample is chosen in the distance interval 120 h −1 Mpc ≤ d ≤ 340 h −1 Mpc (the redshift range 0.04 < z < 0.09) where the selection effects are the smallest (we discuss the selection effects in detail in Tago et al 2010;Einasto et al 2012a). The details of data reduction and the description of the group catalogue can be found in Tempel et al (2012).…”
Section: Galaxy Group and Supercluster Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The morphology of superclusters up to a distance of 340 h −1 Mpc was determined in Einasto et al (2012a) who classified superclusters as filaments and spiders on the basis of their morphological information and visual appearance. The details about supercluster morphology are given in Einasto et al (2007cEinasto et al ( , 2011c.…”
Section: Luminosity Density Field and Superclustersmentioning
confidence: 99%
“…Furthermore, the properties of groups in superclusters, and galaxies in them, can be studied (Einasto et al 2003(Einasto et al , 2011(Einasto et al , 2012Lietzen et al 2012;Krause et al 2013).…”
Section: Introductionmentioning
confidence: 99%